Initiatives for improving delayed discharge from a hospital setting: a scoping review. Issue 2 (11th February 2021) - Cadel, Lauren; Guilcher, Sara J T; Kokorelias, Kristina Marie; Sutherland, Jason; Glasby, Jon; Kiran, Tara; Kuluski, Kerry
Abstract : Objective: The overarching objective of the scoping review was to examine peer reviewed and grey literature for best practices that have been developed, implemented and/or evaluated for delayed discharge involving a hospital setting. Two specific objectives were to review what the delayed discharge initiatives entailed and identify gaps in the literature in order to inform future work. Design: Scoping review. Methods: Electronic databases and websites of government and healthcare organisations were searched for eligible articles. Articles were required to include an initiative that focused on delayed discharge, involve a hospital setting and be published between 1 January 2004 and 16 August 2019. Data were extracted using Microsoft Excel. Following extraction, a policy framework by Doern and Phidd was adapted to organise the included initiatives into categories: (1) information sharing; (2) tools and guidelines; (3) practice changes; (4) infrastructure and finance and (5) other. Results: Sixty-six articles were included in this review. The majority of initiatives were categorised as practice change (n=36), followed by information sharing (n=19) and tools and guidelines (n=19). Numerous initiatives incorporated multiple categories. The majority of initiatives were implemented by multidisciplinary teams and resulted in improved outcomes such as reduced length of stay and discharge delays. However, the experiences of patients and families were rarely reported. Included initiatives also lacked important contextual information, which is essential for replicating best practices and scaling up. Conclusions: This scoping review identified a number of initiatives that have been implemented to target delayed discharges. While the majority of initiatives resulted in positive outcomes, delayed discharges remain an international problem. There are significant gaps and limitations in evidence and thus, future work is warranted to develop solutions that have a sustainable impact.